Development of Tetra-primer Amplification Refractory Mutation System (ARMS) PCR for Detection of CHRNA3 rs8040868 - Anggi Laksmita Dewi; Dewi Kartikawati Paramita; Jajah Fachiroh (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Single nucleotide variations (SNV) have been mapped to be associated with several human conditions and diseases. To validate the association between SNV to certain human traits or diseases, a large number of subjects must be included. Thus, in need of a fast, relatively economic, and reliable genotyping method. This can be achieved through the use of tetra-primer amplification refractory mutation system polymerase chain reaction (Tetra-primer ARMS PCR). This study reports strategy to develop Tetra-primer ARMS PCR-based genotyping of CHRNA3 rs8040868.METHODS: The optimization of Tetra-primer ARMS PCR was done through these steps: identification of gene sequence and position of single mutation; designing outer and inner PCR primers; amplification of target gene fragments through PCR by using outer primer; confirming genotype of the PCR product by using sequencing; determining an optimum ratio of outer and inner primer; and determining optimum annealing temperature and cycles for the PCR program. The PCR products were run in 2% gel agarose electrophoresis and visualized under UV illumination.RESULTS: Outer and inner primer ratio of 1:3 with annealing temperature of 64.4°C and 40x cycles was found to be the most optimum condition. Tetra-primer ARMS PCR was able to confirm the results of the DNA sequence of 2 samples, confirming wild-type variants (TT allele) and the heterozygous mutant (CT allele).CONCLUSION: Tetra-primer ARMS PCR was able to genotype rs8040868 of the CHRNA3 gene.KEYWORDS: tetra-primer ARMS PCR, CHRNA3, rs8040868, genotyping